Le vocabulaire des directions cardinales dans les dialectes du continuum cri-innu-naskapi-atikamekw - Vincent Collette (Journal de la Société des Américanistes)
The aim of this article is to describe the vocabulary of cardinal directions in languages belonging to the geographical branch of Central Algonquian and, particularly, for the dialects belonging to the Cree-Innu-Naskapi-Atikamekw continuum. The analysis of the morphology and the semantics of the words (particles, verbs and nouns) which express cardinal directions shows that these languages use four sources of lexicalization in order to name the cardinal directions: sun cycle, wind direction, river flow, wind/cardinal deity. The data from the Eastern dialects of the Cree-Innu-Naskapi-Atikamekw continuum indicate that in traditional societies the referent which serves as the source of lexicalization for cardinal directions (that is, river flow and sun cycle) is more salient than the direction itself and that some economic, social, cultural and religious changes, provoked by the presence of persons and institutions belonging to the dominant society may accelerate lexical overlaps and replacement in the lexical domain of cardinal directions.